Code-Switching in “Despacito (Remix)”: A Sociolinguistic Perspective in Bilingual and Global Pop Music - Sabtiana, Rela (Universitas Muhammadiyah Mataram, 2025)
In an increasingly globalized world, multilingualism has become a key feature of contemporary popular music. This research investigates the structural forms and communicative functions of language alternation in Despacito (Remix)—a globally successful pop song blending Spanish and English. Drawing on Poplack’s typology of code-switching, Hoffman’s functional motivations, and Muysken’s classifications of code-mixing, the study examines how language alternation shapes the song’s narrative structure, emotional expression, and international appeal. Employing a qualitative descriptive approach, this research conducts a close analysis of the song’s lyrics—particularly Justin Bieber’s bilingual performance—revealing the prominent use of switching within sentences and between sentences, alongside instances of insertional mixing. The findings indicate that language alternation is not merely stylistic choices, but strategic tools to enhance expressiveness, foster cultural hybridity, and expand global reach. In comparison with previous studies on code-switching in Indonesian digital and literary contexts, this paper highlights how popular music represents a distinct and underexplored domain where linguistic creativity intersects with market-driven aesthetics. Ultimately, the study underscores the role of language alternation as a powerful mechanism for shaping narratives, constructing identities, and engaging diverse audiences in global entertainment media.